Pemberdayaan Ekonomi Perempuan Melalui Inovasi Lulur Kolagen dari Sisik Ikan Oreochromis niloticus dan Digitalisasi Pemasaran Produk di PKK Tlogoanyar Lamongan - Muhamad Ganda saputra; Nahardian Vica R; Nuryati (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service program aims to empower the women of the PKK group in Tlogoanyar Village, Lamongan Regency, through the utilization of Oreochromis niloticus fish scale waste into collagen-based body scrub products. The program focuses on three main aspects: production, business management, and digital marketing. The background problem identified includes the underutilization of fish waste with high collagen content, limited technical knowledge in hygienic production, lack of business management capability, and absence of product branding and digital marketing skills. Through this program, a comprehensive empowerment model was implemented combining training, technology adoption, and mentoring for sustainable women-led entrepreneurship. The applied methods consist of socialization, technical training on collagen extraction and formulation of natural scrub products, managerial workshops on micro-enterprise management, and digital marketing training for social media and marketplace engagement. The program also facilitated equipment provision and business legality registration (NIB, P-IRT). The outcomes include: the establishment of a community-based micro business group, production of collagen scrub products, standard operating procedures (SOPs) for production and sanitation, product branding and packaging designs, and the creation of online marketing channels (Shopee and Instagram). The economic impact is reflected in the increased household income of PKK members and reduced organic waste in the community. Socially, it strengthens women's participation and gender equality in local economic development. This initiative demonstrates how local resources and simple technology can be transformed into innovative products with economic and environmental value, supporting the Sustainable Development Goals (SDGs) 1, 5, 8, and 12 through inclusive and sustainable community empowerment.